A correlational investigation of psychological wellbeing, academic self- efficacy, school climate and academic performance among female undergraduate students of University of Ibadan, Nigeria (2016)
Observations reveal that only few exceptional female undergraduates perform at their best in Nigeria institutions, host of others struggle to have good grades. This has lead to more female students’ frustration and dropout rate which attracted an investigation of psychological-wellbeing, academic self efficacy and school climate as correlate of academic achievement of female undergraduate students University of Ibadan. A descriptive research design of the correlational type was adopted for this study. An array of reliable measuring scales was used for the data collection. A sample of 55 female students was randomly selected 200 level guidance and counseling students in the University of Ibadan. The study recorded a significant relationship among the variables through a zero order correlation. A significant joint effect of psychological-wellbeing, academic self efficacy, school climate and academic achievement was found. The most potent factor was academic efficacy; followed by psychological wellbeing, and school climate. This justifies that female undergraduate student academic performance is likely to improve with increased influence of psychological wellbeing, academic self efficacy and good school climate. Therefore, it was recommended that the student affairs should monitor student performing below required and refer them to the counselor. The University counseling unit was enjoined to organized academic booster programmes to enhance the confidence of students towards achieving success. University administrators and the federal government should make all facilities available to make the school environment homely.